The grammatical and semantic connections between Quranic verses - touati, adelaziz (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : ''ilm al-munāsabah'' or the science of the correlation (between the verses and/or surahs) is a discipline that is dedicated to studying the different correlations between parts of the Holy Quran and its branches. These branches include chapters and verses. The aim is both to confirm the contextual arrangement of these parts, as well as to determine their compatibility, coherence, and harmony. This article's objective is to shed light on the various syntactical and semantic correlations between particular Quranic verses, and to assess how cohesively they function, based on either pure syntactical functions or specific semantics.